Myopic macular atrophy in the two-continent population-based study - Jonas, Jost B.; Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Wang, Ya Xing; Xu, Jie; Jonas, Rahul A.; Panda-Jonas, Songhomitra (Investigative ophthalmology & visual science, 2024)
To examine the prevalence of Bruch's membrane defects (BMDs) and subretinal proliferations (SRPs) in highly myopic eyes with myopic macular atrophy (myopic macular degeneration [MMD] stage 4) and myopic patchy atrophies (MMD stage 3) in three ethnically different cohorts recruited in a population-based manner. The Ural Eye and Medical Study (UEMS) and Beijing Eye Study (BES) included individuals aged 40+ years, and the Ural Very Old Study (UVOS) examined individuals aged 85+ years. Main outcome measures were the prevalence of BMDs and SRPs. Among 5794 UEMS participants, 19 eyes had MMD stage 4, with 17 (89%) eyes showing a foveal BMD; two eyes could not fully be explored. All 19 eyes showed localized SRPs. Among 21 eyes with MMD stage 3, BMD and SRP prevalence was 9 of 21 (44%) and 7 of 21 (33%), respectively. Among 930 UVOS participants, 17 eyes had MMD stage 4, with 16 (94%) eyes showing foveal BMDs and SRPs; one eye could not be assessed. Among 18 eyes with MMD stage 3, BMD and SRP prevalence was 3 of 18 (17%) and 2 of 18 (11%), respectively. Among 3468 BES participants, 8 eyes had MMD stage 4, with all eyes showing foveal BMDs and SRPs. Among 14 eyes with MMD stage 3, BMD and SRP prevalence was 10 of 14 (71%) and 7 of 21 (33%), respectively. All eyes with assessable myopic macular atrophy showed foveal BMDs associated with SRPs, while patchy atrophies could be differentiated into those with BMDs and SRPs and those without BMDs and without SRPs. Independent of the MMD stage, the prevalences of BMDs and SRPs were highly significantly associated with each other.
Online veröffentlicht: 23.Juli 2024
Gesehen am 08.04.2025